2007
DOI: 10.1038/nature05700
|View full text |Cite
|
Sign up to set email alerts
|

Effect of natural iron fertilization on carbon sequestration in the Southern Ocean

Abstract: The availability of iron limits primary productivity and the associated uptake of carbon over large areas of the ocean. Iron thus plays an important role in the carbon cycle, and changes in its supply to the surface ocean may have had a significant effect on atmospheric carbon dioxide concentrations over glacial-interglacial cycles. To date, the role of iron in carbon cycling has largely been assessed using short-term iron-addition experiments. It is difficult, however, to reliably assess the magnitude of carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
667
3
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 740 publications
(716 citation statements)
references
References 43 publications
27
667
3
1
Order By: Relevance
“…This is in agreement with the dominance of more or less heavily processed particles (faecalaggregates) during SAZ-Sense and also agrees with many other studies in Polar regions (e.g. Blain et al, 2007;Pollard et al, 2007;Wassmann et al, 2008).…”
Section: Estimates Of Export Efficiencysupporting
confidence: 81%
See 3 more Smart Citations
“…This is in agreement with the dominance of more or less heavily processed particles (faecalaggregates) during SAZ-Sense and also agrees with many other studies in Polar regions (e.g. Blain et al, 2007;Pollard et al, 2007;Wassmann et al, 2008).…”
Section: Estimates Of Export Efficiencysupporting
confidence: 81%
“…This coincides with results from the Kerguelen Ocean and Plateau compared Study (KEOPS) that was carried out in PFZ waters (Blain et al, 2007), where most of the particle flux originated from faecal matter (Ebersbach and Trull, 2008). Similar to our dominating faecal-aggregates, KEOPS reported on aggregates of faecal matter that were responsible for downward POC export.…”
Section: Estimates Of Export Efficiencysupporting
confidence: 75%
See 2 more Smart Citations
“…Over 30 years of research has demonstrated that Fe limitation controls the efficiency of the biological pump and the structure of phytoplankton communities in the SO (e.g., Martin, 1990;Coale et al, 2003;De Baar et al, 2005;Maldonado et al, 2005;Blain et al, 2007;Boyd et al, 2007;Smetacek et al, 2012). However, only the biologically active pool (defined here as bioavailable) is the fraction that can be effectively taken up by microorganisms to support their nutrient-dependent metabolic processes and growth (Hassler et al, 2012).…”
Section: Iron (Fe) Limitationmentioning
confidence: 99%